L2 Teachers’ Professional Development Management - Gavrilova, Elena; Trostina, Kira (European Scientific Journal, ESJ, 2017)
The article focuses on the issue of furthering foreign language (L2) university teachers’ professional development which necessitates viewing in terms of a particular tertiary education institution and the state requirements. Summarizing the experience of the Plekhanov Russian University of Economics (Moscow, Russia) in creating various professional training opportunities for foreign language teachers, the survey examines the L2 teachers’ needs and objectives in professional advancement, as well as motivating factors and preferences for professional development activities. The paper lays the foundation for a new a 7+Cs evaluation framework to determine the successful management of university-based language teacher training. Recommendations for further improvement of continuous teacher coaching and enhancing their efficiency are developed upon the analysis of the 7+Cs scale.